The Hematoma Evacuation Score: Reducing Thirty-Day Postoperative Mortality in Intracranial Subdural and Epidural Hematomas. (1st September 2019) - Rock, Andrew K; Poulos, Nora Tocheny; Carr, Matthew T; Dincer, Alper; Opalak, Charles F; Broaddus, William C
Abstract: INTRODUCTION: Craniotomy and craniectomy are commonly performed for intracranial subdural and epidural hematoma evacuation and are associated with high mortality, due to the nature of the pathology. The authors developed the validated Hematoma Evacuation Score to identify patients at higher risk of 30-d mortality after craniotomy or craniectomy for subdural or epidural hematoma evacuation. METHODS: A retrospective review was performed on all patients who underwent craniotomy or craniectomy for subdural or epidural hematoma evacuation from the 2005 to 2015 American College of Surgeons National Surgical Quality Improvement Program. Outcomes included any morbidity, major complications, prolonged length of stay (LOS), and mortality. Multivariable logistic regression modeling was used to identify risk factors associated with mortality. The final Hematoma Evacuation Score was validated using bootstrap replications and area under the receiver operating characteristics curve (AUC) calculation. RESULTS: There were 3252 cases (supratentorial: 2943 and infratentorial: 309) of subdural or epidural hematoma evacuation. Odds of mortality were not significantly increased in infratentorial hematoma evacuation compared to supratentorial evacuation (OR: 1.18; 95% CI: 0.84-1.64; P  = .35), and there were no significant differences for the other primary outcomes based on location of evacuation. Independent risk factors for mortality included: age, white race, diabetes, functional dependence, ventilator dependence, dialysis, disseminated cancer, bleeding disorder, emergency surgery, white blood cells (WBC) > 10.0, platelet count < 150, and INR > 1.2. The Hematoma Evacuation Score utilized these risk factors to predict mortality from 1.5% to 95.6% for scores ranging from 0 to 36, respectively (AUC = 0.83). CONCLUSION: The Hematoma Evacuation Score was derived as a validated tool for predicting 30-d mortality following craniotomy or craniectomy for subdural or epidural hematoma evacuation. It relies upon readily available preoperative risk factors and may assist with decision-making and counseling families on postoperative outcomes in patients who may have poor outcomes despite surgical intervention.